PHARMACOLOGICAL EVALUATION OF TRADITIONAL HERBAL REMEDIES USED IN TYPE 2 DIABETES: THERAPEUTIC INTEGRATION IN COMPLEMENTARY TREATMENT - Akbarov Asliddin; Matkarimova Gulnaz (Western European Studies, 2025)
Type 2 diabetes (T2D) is a chronic endocrine disorder characterized by insulin resistance and impaired glucose metabolism. While conventional therapies primarily focus on pharmacological interventions, there is increasing interest in complementary approaches, particularly the use of traditional herbal remedies. This study aims to evaluate the pharmacological properties of selected herbal remedies used in the management of T2D, with an emphasis on their therapeutic integration into conventional treatment strategies. A comprehensive review of literature was conducted to identify herbs commonly used in folk medicine, such as Cinnamomum verum, Ginseng, and Gymnema sylvestre. The pharmacological activities of these herbs, including anti-hyperglycemic, anti-inflammatory, and insulin-sensitizing effects, were examined in preclinical and clinical studies. The findings suggest that these herbal remedies can support glucose regulation, enhance insulin sensitivity, and reduce diabetes-related complications when integrated into standard medical care. However, further clinical trials are needed to confirm the efficacy, safety, and long-term benefits of these herbal interventions.
Keywords: T2dm; traditional; therapies